(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The switched reluctance motor has used in high performance motor control application such as aircraft starter or generator system, electric traction, mining drives, washing machines, door actuators, etc. this use is due to high reliability, high torque, robust construction, low cost of switched reluctance motor. In all applications of switched reluctance motor smooth torque is the major need but due to air gap flux harmonics increases torque ripples further increases periodic speed ripples in switched reluctance motor. Due to this, performance of drive deteriorates. The main and major objective of this paper is to analyse speed control method of switched reluctance motor with pi and fuzzy controller in MATLAB/Simulink environment. Simulation will be carried out with pi and fuzzy controller for reduction of periodic speed ripples in switched reluctance motor. Fuzzy logic controller is introduced to give an effective and outstanding performance to minimize periodic speed ripples in switched reluctance motor.